Development of Volleyball Game Model Using Learning Media - Asep Suharta; Dewi Endriani; Rahma Dewi; Amir Supriadi (UNIB Press, 2022)
The purpose of this study was to develop a volleyball game model using instructional media for junior high school students. The method used in this research is to use the R & D research method which is used to develop a product in the form of a volleyball game model and test the effectiveness of the product. The type of research used in this research is to use mixed methods (qualitative and quantitative) by using the t test on the effectiveness test. The data collection technique in this study was using a questionnaire questionnaire. The subjects used in this study were class VII students of SMP Gajah Madah Medan, totaling 40 students. The results of the small group trial were carried out on 15 junior high school students in class VII-1 with a very good category. The large group trial was conducted on 25 students of SMP Gajah Madah Medan class VII-2 with a very good category. The product effectiveness test was carried out by conducting pre-test and post-test with the results of the t-test p<0.005, this result showed that there was a significant difference. The average pretest score before students use the game model using learning media is 5.42. And after the students were given treatment, namely the volleyball game model using learning media, the average post-test score was 7.71.